Potato yield gaps across the rainfed Yin-mountain Hilly Area of China - Li-guo JIA; Yang CHEN; Yong-lin QIN; Rui-fang LIANG; Shi-xin CUI; Zhong MA; Ming-shou FAN (Journal of Integrative Agriculture, 2018)
Yin-mountain Hilly Area is one of the ideal regions for potato (Solanum tuberosum) production in China. However, potato yield is severely limited as a result of rain-fed crop mode due to water deficiency, as well as an inadequate farming practices. In this study, yield gaps were determined by using attainable yield (Ya) as a benchmark under optimized management practices, i.e., micro-ridge and side planting with plastic-mulching (MS), and flat planting with plastic-mulching (PM). The yields under MS and PM modes are defined as Ya1 and Ya2, respectively. Under the same field with MS and PM modes but different densities and fertilizer usages and so on, it was defined as simulated farmers' practices. The yield of simulated farmers' practices (Yf1) reached 57.3 and 69.6% of Ya1 and Ya2, respectively, while the average yield of 298 randomly surveyed farmers (Yf2) reached only 37.0 and 47.8% of Ya1 and Ya2 for rain-fed potato, respectively. The gaps of water use efficiency exhibited similar pattern. Further analysis shows that improper measures in rainwater conservation and accumulation, and other management practices contributed to 18.5, 18.2, and 42.6% of yield gap between Ya1 and Yf2. Improper nutrition management, including overuse of nitrogen and the deficiency of phosphorus and potassium supplication, was one of the important reasons of yield gap. The results indicate the possibilities of increasing rain-fed potato yields by optimized water and fertilizer managements in the Yin-mountain Hilly Area.